2021
DOI: 10.1186/s41039-021-00167-7
|View full text |Cite
|
Sign up to set email alerts
|

CourseQ: the impact of visual and interactive course recommendation in university environments

Abstract: The abundance of courses available in a university often overwhelms students as they must select courses that are relevant to their academic interests and satisfy their requirements. A large number of existing studies in course recommendation systems focus on the accuracy of prediction to show students the most relevant courses with little consideration on interactivity and user perception. However, recent work has highlighted the importance of user-perceived aspects of recommendation systems, such as transpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…By learning from previous grades, they estimated the students' grades in future courses. Ma et al (2020) studied the reasons for course selection in universities; they found that getting relatively higher grades was one of the factors that influenced learners' choices. Based on learners' previous grades, they estimated how prepared they were for the upcoming courses.…”
Section: Learners' Previous Enrolment and Performancementioning
confidence: 99%
“…By learning from previous grades, they estimated the students' grades in future courses. Ma et al (2020) studied the reasons for course selection in universities; they found that getting relatively higher grades was one of the factors that influenced learners' choices. Based on learners' previous grades, they estimated how prepared they were for the upcoming courses.…”
Section: Learners' Previous Enrolment and Performancementioning
confidence: 99%
“…For instance, in the scenario involving a Career interestbased CRS, the AI could explain to students: "This course is recommended because it aligns with your career interests in machine learning engineering, which could significantly benefit your future career path based on your current academic and extracurricular profile". As students interact with the AI-based CRS's reasoning during evaluations, they will have the chance to develop their own perspectives and improve their capacity to assess and select courses autonomously [48].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Thirdly, AI-based CRSs should provide unexpected or serendipitous course suggestions. This strategy tackles the filter bubble problem by urging students, especially those uncertain about their academic path, to venture into new domains [48]. These recommendations have the potential to expand students' perspectives, exposing them to unfamiliar subjects and revealing interests they may not have previously considered.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Study [21] designed an interactive system to recommend suitable courses to university students based on their interest and popularity of the course. The recommendation is based on historical enrollment data, course descriptions, topic, instructor, and time of study.…”
Section: A Ai-based Solution For Study Plansmentioning
confidence: 99%
“…Studies have investigated the use of machine learning for recommending courses to students [21] as well as including features personal traits [20], and student preferences [19]. While this type of model is suitable for online courses with a large number of enrollments and course choices, this model does not work for the institution of study.…”
Section: A Ai-based Solution For Creating Study Plansmentioning
confidence: 99%